Vulvo-vaginites: tratamento com ducha de hipoclorito de sódio - Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 1994)
A randomized doubel-blind triai was conducted to compare sodium hypochlorite with placebo in the treatment ofthe vaginal infection. The study has comprised 85 patients in the reproductive period of life women who where attended at Sexually Transmitted Diseases Sector (MIP/CMB/CCM) of Universidade Federal Fluminense. The patients were randomly assigned to one of two study groups. ln one group, forty-two patients were treated with 250 m1 of stabilised 750 ppm solution (750 mg/1 or 0,075%) of sodium hypochlorite. Forty-three patients in the other group received bi-destilled water. The placebo and triai solution were applied daily by vaginal douche for ten days. Before and after treatment, patients were evaluated by microbiological analysis, colposcopy, colpocytopathology, and determination ofblood leveis ofNa+, CI- and K+. Before the collection ofthe material we did the identification, the anamnesys and the clinicai history of the patients. The patients that have used vaginal medication and systemic antibiotics or corticoids during the last fifteen days were not included in the study. We also excluded from the work women who had menstruated during the applications or those who did not return for control in the proposed period. Ali the material used in this study was offered to us by researches that gave us the complete instructions about the way to use it. The results showed that 32 of 42 patients (76,19%) of the study group had an increasing recuperation as compared with 2 of 43 patients (4,66%) ofthe placebo group.